Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.5141/jefb.2010.33.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Changes in terpenes of three kinds of pine needles during litter decomposition

Abstract: This study was designed to evaluate changes in the terpene composition of 3 types of pines (Pinus densiflora, Pinus thunbergii and Pinus rigida), while decomposing their leaf litter. Needle litters were placed at two different organic layer depths, one on the surface and the other beneath the litter layer. Changes in the terpene composition of this litter were detected using a gas chromatograph-mass spectrometer. Among the monoterpenes acquired from the fresh needles of P. densiflora and P. rigida, α-pinene (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Jiri are located at similar latitudes, 35°04′N and 35°3 7′N respectively, thus, these results indicate that monoterpene emission from P. densiflora may be affected by the latitude of the location where the trees have grown in the summer. Despite some variations in monoterpene ratios, other studies also confirmed that three monoterpenes from P. densiflora, α-pinene, myrcene, and β-phellandrene are dominantly emitted regardless of location or season in Korea , Jo and Kim 2010, Son et al 2012. The dominant emission of the three monoterpenes from P. densiflora was also observed in studies conducted overseas: an emission experiment performed with cultured P. densiflora in a greenhouse in Japan demonstrated high emission of α-pinene, myrcene, and β-phellandrene (Yokouchi and Ambe 1984).…”
Section: Terpenes From Dominant Tree Species In Korean Forestsmentioning
confidence: 90%
“…Jiri are located at similar latitudes, 35°04′N and 35°3 7′N respectively, thus, these results indicate that monoterpene emission from P. densiflora may be affected by the latitude of the location where the trees have grown in the summer. Despite some variations in monoterpene ratios, other studies also confirmed that three monoterpenes from P. densiflora, α-pinene, myrcene, and β-phellandrene are dominantly emitted regardless of location or season in Korea , Jo and Kim 2010, Son et al 2012. The dominant emission of the three monoterpenes from P. densiflora was also observed in studies conducted overseas: an emission experiment performed with cultured P. densiflora in a greenhouse in Japan demonstrated high emission of α-pinene, myrcene, and β-phellandrene (Yokouchi and Ambe 1984).…”
Section: Terpenes From Dominant Tree Species In Korean Forestsmentioning
confidence: 90%
“…The shed of aged or damaged needles in pine stands is important for the release of VOCs from the forest floor (Isidorov et al, 2003. Even when senescent or dead, pine needles contain high levels of terpenes and other precursors of the oxidized volatile compounds, formed as a result of enzymatic reactions (Isidorov et al, 2010;Jo and Kim, 2010;Zhang et al, 2018). Coniferous litter is also a good source of secondary metabolites that are released during chemical or biological decomposition processes.…”
Section: Introductionmentioning
confidence: 99%